1978
DOI: 10.1159/000232064
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Anaphylaxis in the Rat after Sensitisation with Mouse Antiserum

Abstract: Passive peritoneal anaphylaxis in rats, sensitised with mouse antiserum, had characteristics of an IgE-mediated reaction, in that the serum was heat-labile and pretreatment of the rats with disodium cromoglycate (DSCG), or sodium nivimedone, inhibited the release of both histamine and slow-reacting substance of anaphylaxis (SRS-A). Sodium nivimedone was more potent than DSCG as an inhibitor of histamine release. Peak concentrations of histamine and SRS-A in the peritoneal fluids of the rats, were reached withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Rat anti serum containing IgG2;, antibody can also sensitise for a mast cell dependent release of histamine and SRS-A, but this activity was not found when the sera contained high lev els of non-specific IgG2a, which presumably competed with antibody for receptors on the mast cell [18]. Rat IgE antibody sensitised for a mast cell dependent release of histam ine and SRS-A [18] and similar effects were obtained with the use of mouse antiserum containing IgE antibody [24]. Following an tigen challenge of rats, sensitised with mouse or rat antiserum containing IgE anti body, there was an increase in concentra tions, in the peritoneal fluids, of histamine, SRS-A and extravasated dye-labelled plas ma proteins.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Rat anti serum containing IgG2;, antibody can also sensitise for a mast cell dependent release of histamine and SRS-A, but this activity was not found when the sera contained high lev els of non-specific IgG2a, which presumably competed with antibody for receptors on the mast cell [18]. Rat IgE antibody sensitised for a mast cell dependent release of histam ine and SRS-A [18] and similar effects were obtained with the use of mouse antiserum containing IgE antibody [24]. Following an tigen challenge of rats, sensitised with mouse or rat antiserum containing IgE anti body, there was an increase in concentra tions, in the peritoneal fluids, of histamine, SRS-A and extravasated dye-labelled plas ma proteins.…”
Section: Introductionmentioning
confidence: 62%
“…Following an tigen challenge of rats, sensitised with mouse or rat antiserum containing IgE anti body, there was an increase in concentra tions, in the peritoneal fluids, of histamine, SRS-A and extravasated dye-labelled plas ma proteins. Sufficient histamine was re leased to mediate 60-80% of the extravasa tion produced, and the remainder may have been mediated by SRS-A [21,24], 5-Hydroxytryptamine (5-HT) was not a direct mediator of extravasation in these systems [221. Guinea pig antiserum sensitised the peri toneal cavity of the rat in a similar manner to rabbit antiserum in that antigen challenge released SRS-A without the release of hist amine. It was suggested that the source of the SRS-A in this system was the platelet and not the polymorphonuclear leucocyte [9]We have sensitised the peritoneal cavi ties of rats with guinea pig antiserum and have determined the effects of subsequent andgen challenge on the concentrations, in the supernatants of peritoneal washings tak en from the rats, of SRS-A, histamine, 5-HT and of extravasated dye-labelled plas ma proteins.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the serum used for passive sensitisation causes an infiltra tion of neutrophils [14], so that cell studies in the rat peritoneal cavity were most readi ly carried out in actively sensitised animals. The infiltration of neutrophils into the peri toneal fluid of the actively sensitised rats following antigen challenge followed a simi lar pattern to that described by Capasso el al.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been made of the me diators and cell counts during reversed pas sive Arthus reactions in the pleural cavities of rats [18]. Mediator release and extrava sation of plasma proteins have been studied in passive peritoneal anaphylaxis in the rat [13], but cellular studies in that model were difficult since the sensitisation alone in duced changes in the cell content of the per itoneal cavity [14]. The present study in ac tively sensitised rats challenged by intraperi toneal injection of antigen has made possi ble an investigation of the kinetics and in terrelationships of the release of pharmacol ogical mediators, extravasation of plasma proteins, enzyme levels and changes in cell content of the peritoneal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Passive sensitisation of rats by intraperitoneal injection with rat antiserum produces inflammation in their peritoneal cavities as demonstrated by an increase in numbers of neutrophil polymorphonuclear leucocytes [21], high background levels of material as saying as 5-HT and a tendency to hypersen sitivity to the increase in vascular permea bility produced by injection with histamine. There is little 5-HT presents in human mast cells and 5-HT has relatively little effect on human bronchial strip [5]; therefore, it is not thought to be an important mediator of allergic asthma.…”
Section: Discussionmentioning
confidence: 99%